Evaluating The effects of lipopolysaccharides and hydrogen peroxide on human and mouse astrocytes in vivo and in vitro, in relation to Alzheimer’s Disease - Sivaram, Anjali (2024)
Alzheimer’s disease is a neurodegenerative disease characterised by gliosis, decreased neuronal cell viability, cognitive impairment, as well as increased amyloid beta levels, cytokine expression and oxidative stress. These symptoms have been seen in in vivo and in vitro studies that have utilised LPS, inflammatory endotoxins that are derived from gram-negative bacteria. Moreover, these are found at elevated levels co-localised with amyloid plaques and astrocytes in the brains of AD patients. Given its ability to mimic or exacberate such neuroinflammatory changes, and its relevance in AD pathology, this study looks at leveraging LPS to stimulate astrocytes in vivo using intranasal LPS, and in vitro, using the astrocytic SVG-A cells. These models can then be used in the future to test novel anti-inflammatory therapies against AD.